2022
DOI: 10.1038/s41598-022-26530-2
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ating enzymes cooperate to coordinate development

Abstract: The transcriptome is subject to rapid and massive changes during the transition between developmental stages. These changes require tight control to avoid the undesired reactivation of gene expression that is only important for previous developmental stages and, if unchecked during transition between developmental stages, could lead to anarchic proliferation and formation of malignant tumors. In this context, the involvement of chromatin factors is important since they can directly regulate the expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…4B). These results, in addition to those of our previous study (14), show that PARG and PARP1 play both direct and complementary roles to regulate the transcription program involved in the transition from larval to pupal stage.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…4B). These results, in addition to those of our previous study (14), show that PARG and PARP1 play both direct and complementary roles to regulate the transcription program involved in the transition from larval to pupal stage.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, we found that PARG and PARP1 bind together to the promoter region of the transcription factors involved in ecdysone mid-response (Supplemental Table S1). Their expression is not signi cantly affected in parg and parp1 mutants, but most are downregulated (14). Together, these results suggest that PARP1 and PARG might play a role in the ecdysone mid-response.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations